Development of an Enrichment Book with Hematite as a Battery Electrode in Renewable Energy Learning - Rosyidi, Farisa Ramadhani; Suharno, Suharno; Harjunowibowo, Dewanto (Universitas Sebelas Maret, 2024)
Learning innovation is needed to maximize interaction between teachers and students so that learning is much more effective and efficient, one of which is through enrichment books so that students learn not only theory but also its application. Enrichment books were developed to enrich students' knowledge. In this research, an enrichment book will be created using hematite as a battery electrode in renewable energy learning. The aim of this research is to determine the development and feasibility of enrichment books using hematite as battery electrodes in renewable energy learning. Enrichment books are an innovation in education that was developed to enrich information that is not obtained from textbooks. The method used in this research is R&D. The research was carried out using the ADDIE model, but this research was limited to the development stage. The enrichment book was developed using the Canva application. The data collection technique was carried out using a purposive sampling technique. The enrichment book that has been created is validated by distributing questionnaires to expert validators and practitioner validators. The research was conducted at three schools in the Greater Solo area, namely S MA N Kebakkramat, MA Al Madinah Nogosari, and SMK Batik 2 Surakarta. The results obtained show that the enrichment book with hematite as a battery electrode can be applied in physics learning on renewable energy materials with a validation score of 68.41 or perfect criteria. This research can be the basis for developing enrichment books using hematite as battery electrodes in Renewable Energy learning.